Online Influence Pathways: A Study of Celebrity Endorsements and EWOM Effects on Purchase Intention Via Brand Trust - Setiyawan, Agus; Setyabudhi, Irwan; Nurdin, Mohamad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of Celebrity Endorsements and Electronic Word-of-Mouth (eWOM) on Brand Trust and Purchase Intention. A quantitative design was employed with 385 respondents who actively search for online product reviews and follow Celebrity Endorsements. Data analysis was conducted using structural equation modeling to assess both direct and indirect relationships among variables. The findings reveal that Celebrity Endorsements significantly strengthen Brand Trust, particularly in the dimensions of benevolence, empathy, and honesty, and also directly enhance Purchase Intention. Electronic Word-of-Mouth (eWOM) positively affects Brand Trust and contributes to Purchase Intention as well. Furthermore, Brand Trust was found to mediate the relationships between Celebrity Endorsements, Electronic Word-of-Mouth (eWOM), and Purchase Intention, with indirect effects also proving significant. These results highlight that both direct and indirect effects play a crucial role, suggesting that effective marketing strategies should integrate Celebrity Endorsements and consumer-generated eWOM while prioritizing the development of brand trust to drive Purchase Intention.